The Correlation Fast Food Consumption Habits and Students’ Learning Concentration in Grade X and XI SMA Hasanka Boarding School Palangka Raya - Bintang Suati; Eva Prilelli Baringbing; Anggreni Ade (PROMOTOR, 2026)
Background: Fast food, has high contain of salt, sugar, saturated fat, and calories but low in essential nutrients such as protein, vitamins, and minerals, can have a negative impact on cognitive function, including learning concentration. Excessive consumption of this type of food can lead to unstable energy drops, metabolic disorders, and other health problems, ultimately affecting the brain's ability to concentrate and process information optimally. Objective: To determine the correlation between fast food consumption habits and students learning concentration correlation in grades X and XI at SMA Hasanka Boarding School Palangka Raya. Methods: Observational Analytic with a Cross-Sectional approach. The sampling technique was total sampling, involving all 73 students in grades X and XI. The analyses performed were univariate and bivariate analyses using the Chi-Square test. Results: The research showed a Chi-Square Test p-value of 0.000 < 0.05, indicating a correlation between fast food consumption habits and students learning concentration correlation in grades X and XI at SMA Hasanka Boarding School Palangka Raya. Conclusion: Students with low fast food consumption habits tend to have good concentration in learning, while students with high fast food consumption habits tend to have poor concentration in learning. Students were expected to limit their consumption of fast food such as fried foods, instant noodles, and other processed foods. It was better to choose balanced nutritious foods that contain protein, fiber, vitamins, and minerals.